PERLINDUNGAN HUKUM BAGI PEMBELI TERKAIT AKTA PERJANJIAN PENGIKATAN JUAL BELI YANG OBJEKNYA TIDAK DILAKUKAN PENGECEKAN KEPEMILIKANNYA OLEH NOTARIS - Azmi Ansyari; Felicitas Sri Marniati; Mulyadi Mulyadi; Mulyadi (Journal of Innovation Research and Knowledge, 2026)
The increasing number of land and building transactions has led to the frequent use of Sale and Purchase Binding Agreements (PPJB) prior to the execution of a formal deed of sale and purchase. However, in practice, such agreements are often drawn up without prior verification of land ownership by the notary. This situation creates a risk of legal disputes and potential losses for good-faith buyers if the land is later found to be under dispute or encumbered with third-party rights. The research problems addressed in this study are: how the legal liability of a notary arises in relation to a Sale and Purchase Binding Agreement drawn up without prior verification of ownership, and how legal protection can be afforded to buyers in connection with such agreements, analyzed through the theory of legal protection as proposed by Satjipto Rahardjo and the theory of liability as articulated by Hans Kelsen. The method used in this research is normative juridical research, namely legal research based on library materials or secondary data, consisting of primary, secondary, and tertiary legal materials. The research approaches employed include the statutory approach, case approach, analytical approach, and conceptual approach. The collection of legal materials is carried out by identifying and inventorying positive legal norms, book literature, journals, and other legal sources. The analysis of legal materials is conducted through legal interpretation, namely grammatical interpretation and systematic interpretation, as well as methods of legal construction, including analogical construction and legal refinement. The findings indicate that the execution of a PPJB without prior verification of land ownership constitutes a violation of the prudential principle that must be observed by notaries in performing their official duties. In such circumstances, notaries may be held legally liable under civil, administrative, and professional ethical frameworks if their negligence causes losses to the buyer. Furthermore, good-faith buyers remain entitled to legal protection through civil remedies, including claims for damages, annulment or degradation of the evidentiary value of the deed, and legal actions against responsible parties.